Evaluation of dexmedetomidine and fentanyl as additives to ropivacaine for epidural anesthesia and postoperative analgesia - S Kiran; Kavita Jinjil; Urvashi Tandon; Soumita Kar (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: The synergism between epidural local anesthetic agent and opioids is well established, but evidence for the combination of local anesthetic agent with dexmedetomidine in epidurals is limited. This study evaluates the clinical efficacy of dexmedetomidine versus fentanyl as an additive to ropivacaine for epidural anesthesia. Material and Methods: Patients undergoing infraumbilical surgeries were divided randomly into three groups - Group R (n = 25): received 18 ml of 0.5% ropivacaine for epidural anesthesia and 10 ml of 0.1% ropivacaine boluses for postoperative analgesia; Group RF (n = 25): received 18 ml of 0.5% ropivacaine with 20 μg fentanyl for epidural anesthesia and 10 ml of 0.1% ropivacaine with 10 μg fentanyl boluses for postoperative analgesia; and Group RD (n = 25): received 18 ml of 0.5% ropivacaine with 10 μg dexmedetomidine for epidural anesthesia and 10 ml of 0.1% ropivacaine with 5 μg dexmedetomidine boluses for postoperative analgesia. Results: The mean time for onset of sensory block, in minutes, was 18.6 ± 4.4 in R Group, 12.8 ± 1.8 in RF Group and 10.8 ± 2.7 in RD Group (P < 0.001). There was a statistically significant difference with regard to degree of motor block, with RD Group faring better than RF Group and R Group. The mean time to rescue analgesia, in minutes, was 139.8 ± 21.4 in Group R, 243 ± 29.7 in Group RF, and 312.4 ± 30.2 in Group RD (P < 0.001). Incidence of hypotension at 10 min was 4% and 48% in RF and RD Groups, respectively (P < 0.001). Conclusions: Epidural anesthesia achieved with 10 μg dexmedetomidine as an additive to 0.5% ropivacaine is more effective with respect to duration and intensity of analgesia when compared to 0.5% ropivacaine alone or addition of 20 μg fentanyl to 0.5% ropivacaine.